Consecutive Laparoscopic En-Block Left Pancreato-Nephro-Splenectomy and Later Pancreaticoduodenectomy: Pushing Back the Limits of Laparoscopic Pancreatic Resections - Poves, Ignasi; Burdio, Fernando; Frances, Albert; Grande, Luis (JOP. Journal of the Pancreas, 2015)
Context Laparoscopic distal pancreatectomy is a widely accepted treatment for non-malignant lesions of the left pancreas. However, the role of laparoscopy in more complex procedures such as pancreaticoduodenectomy or treatment of pancreatic adenocarcinoma remains controversial. Case report A seventy-seven-year-old woman underwent surgery twice: first for a PADC of the tail infiltrating the spleen and left kidney, and then for a second PADC of the neck and head of the pancreas diagnosed during follow-up (11 months) of the first tumor. In both procedures a totally laparoscopic approach was applied. The first procedure was an en-bloc resection including the left kidney, spleen and left pancreas. Final diagnosis showed a PADC (49x42x40 mm) involving one of the 17 lymph nodes harvested (R0). Postoperative course was uneventful, and lasted five days. Later, due to the appearance of a new tumor in the right pancreas, an extended pylorus-preserving PD was performed with the patient in supine position with the legs apart. In the postoperative period she presented chylous ascites and required hospitalization for 17 days. Definitive biopsy showed a 2 cm PADC (PanIn 2 and 3 lesions in the rest of the gland). Two out of 21 nodes isolated were found to be affected (R0). No chemotherapy was administered after the second operation. Conclusions Our report may help to redefine the limits of laparoscopy in pancreatic oncologic surgery. It describes several features of added technical difficulty, and may prompt further reflection on the current limits and indications of laparoscopic pancreatectomy. Image: Positioning of the trocars and incision.